Propagation measurement in IMT-2000 band in Malaysia environment - Abdul Rahman, Tharek; Gan, Beng Ser (2000)
The mobile radio channel is one of the factors, which limits the performance of wireless communication systems. The radio path (the path between the transmitter and receiver) can vary from a simple line-of-sight (LOS) to one that is blocked by mountains. The performance of wireless channels is hard to predict compared to wired channels. A propagation measurement has been carried out in conjunction with the W-CDMA (wideband code division multiple access) field trial in Malaysia. The main objective of the measurement is to determine the performance of the W-CDMA system in Malaysia environment. The system performance is evaluated base on the bit error rate (BER). The pathless exponent (propagation power law) was also investigated. The BER measurement was based on the BER on the downlink of the base transceiver system (BTS)